2016
DOI: 10.1007/s11104-015-2788-7
|View full text |Cite
|
Sign up to set email alerts
|

Soil physicochemical properties and floristic composition of two ecosystems differing in plant diversity: fallows and meadows

Abstract: Background and aims European farmland has been abandoned at an unprecedented rate over the last few decades, resulting in an increase of the area of fallows and a decrease in plant diversity in meadows. This work was aimed at determining whether differences in the persistence and plant diversity of the two ecosystem types, similar in plant biomass and geographical location, resulted in changes in soil physicochemical properties. Methods Soil physicochemical properties and floristic composition were studied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In the case of forest clearings this process may last a long time (Winsa et al, 2015). One factor that may influence species composition on former arable land is cultivation procedures, particularly fertilizers that alter the chemical and physical properties of the soil (Chmolowska et al, 2016). For this reason many studies have found that the species composition of grasslands depends on how long the land has been used as grassland (Pitkänen et al, 2016, Purschke et al, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of forest clearings this process may last a long time (Winsa et al, 2015). One factor that may influence species composition on former arable land is cultivation procedures, particularly fertilizers that alter the chemical and physical properties of the soil (Chmolowska et al, 2016). For this reason many studies have found that the species composition of grasslands depends on how long the land has been used as grassland (Pitkänen et al, 2016, Purschke et al, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…For fallows, the indicators were the presence of ruderal and segetal weeds, especially couch grass Elymus repens and low plant diversity-less than 27 species per 25 m 2 . The meadows had a higher richness, with 35-50 plant species per 25-m 2 plot, and a high proportion of species characteristic for the Molinio-Arrhenatheretea class and also of legumes (Chmolowska et al 2016). The fallow soils had much higher contents of nitrates and available P and K than meadow soils and a slightly lower water-holding capacity and C: N ratio (Chmolowska et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The meadows had a higher richness, with 35-50 plant species per 25-m 2 plot, and a high proportion of species characteristic for the Molinio-Arrhenatheretea class and also of legumes (Chmolowska et al 2016). The fallow soils had much higher contents of nitrates and available P and K than meadow soils and a slightly lower water-holding capacity and C: N ratio (Chmolowska et al 2016). Apart from that, the soils did not differ between ecosystem types in total C, N, Ca, Na, Mn, NH 4 + , organic matter (OM), sand, silt, fine contents, and cation exchange capacity (CEC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CCA focused on scaling inter-species correlations, and Hill's scaling type was used. Monte Carlo tests with 1000 permutations were run, as suggested for P = 0.05 (Chmolowska et al 2016), to determine which environmental variables significantly affect vegetation structure. P values were identified by querying the critical values for correlation efficient.…”
Section: Discussionmentioning
confidence: 99%